Generic antibiotic industries: Challenges and implied strategies with regulatory perspectives - M Venkatesh; V G Bairavi; K C Sasikumar (Wolters Kluwer Medknow Publications, 2011)
Ever since the discovery of antibiotics, the quality of human life greatly improved in the 20 th century. The discovery of penicillin transformed the medicine industry and initiated a search for a better antibiotic every time resulting in several synthetic and semi-synthetic antibiotics. Beginning with the 1937 sulfa drug tragedy, the drug regulations had a parallel growth along with the antibiotics and the antibiotic-based generic Pharma industries. This review article is focused on the scenario depicting current global Pharma industries based on generic antibiotics. Several regulatory aspects involved with these industries have been discussed along with the complexity of the market, issues that could affect their growth, their struggle for quality, and their compliance with the tightened regulations. With the skyrocketing commercialization of antibiotics through generics and the leveraging technologic renaissance, generic industries are involved in providing maximum safer benefits for the welfare of the people, highlighting its need today.